РОЗВИТОК КРИТИЧНОГО МИСЛЕННЯ СТАРШОКЛАСНИКІВ НА УРОКАХ ІСТОРІЇ (Zaporizhzhia Historical Review, 2021)
The problem of concept "critical thinking" is considered in the paper. Author is analyzing conditions promoting the pupil's critical thinking in learning Humanities. There are components and forming stages of critical thinking in author's research. The clause consists report about ascertain pedagogical experiment with the aim to define the level of critical thinking skills. The results of ascertain pedagogical experiments indicated that the pupils of senior forms have unsatisfactory skills of critical thinking: they don’t always prove their ideas, show prejudice, they cannot see contradictions. Author's forming critical thinking procedure is represented in the article.